Answers
Answered by
4
Heya !!!
This is your answer..
Given :-
![(y - \frac{x}{10} )(y + \frac{x}{10} ) (y - \frac{x}{10} )(y + \frac{x}{10} )](https://tex.z-dn.net/?f=%28y+-++%5Cfrac%7Bx%7D%7B10%7D+%29%28y+%2B++%5Cfrac%7Bx%7D%7B10%7D+%29+)
Using identity..
(a - b) (a +b ) = a² - b²
So,
(y - x/10) (y + x/10) = y² - (x/10)²
= y² - x²/100
Hope It Helps
This is your answer..
Given :-
Using identity..
(a - b) (a +b ) = a² - b²
So,
(y - x/10) (y + x/10) = y² - (x/10)²
= y² - x²/100
Hope It Helps
Similar questions
Computer Science,
9 months ago
Hindi,
9 months ago
Math,
9 months ago
Math,
1 year ago
Social Sciences,
1 year ago
Science,
1 year ago